The Silent Way Method in Learning Arabic - Budi Santoso Wibowo; Nurhabibah Harahap (Lembaga Pengembangan Kinerja Dosen, 2022)
The Silent Way method (al-tharīqah al-Shāmitah) was discovered by a language learning expert named Caleb Gattegno (1972), who applied philosophy and cognitivism principles in his learning. This study aims to determine the extent to which the Silent Way method can be used in learning Arabic. This research was conducted by library research by collecting some empirical documents. The results of this study reveal that in using the Silent Way method, an educator must speak a little during the learning process in class. But that does not mean not doing anything during the learning process. Using various learning media, this method is based on a rule that educators should be silent so that students can express their opinions as widely as possible.